UNDERSTANDING CREATIVE ECONOMY CONCEPT THROUGH INNOVATION ADOPTERS PERSPECTIVE - Ayu, Aulia Suminar; Dwihantoro, Prihatin; Lokantara, I Gede Wyana (Komunikator, 2020)
This research is part of Creative Economy Sub-Sector?s Mapping and Clustering in Kendal Regency. The research aims to describe stakeholder understanding (refers to Kendal Regency Government) towards the creative economy concept using diffusion of innovation theory. The diffusion of innovation is used because Kendal Regency Government is still not familiar with the concept of the creative economy. This qualitative descriptive research used interviews, observation, FGD, and literature study as the method to gather data. Results showed that from 229 SME labeled with the creative economy by Youth, Sports, and Tourism Department, Kendal Regency only 66 of them that met Creative Economy Agency (Badan Ekonomi Kreatif- BEKRAF) criteria. This means that the officials' understanding of the concept of the creative economy is not yet comprehensive. The creative economy is essential to shape the image of the regency (city branding). On the other hand, Kendal Regency had a program to improve the image of the city as a form of smart branding. Smart Branding was a derivation of the Smart City Kendal master plan in 2018-2028. The lack of relevant data in the Kendal District Government showed that the desire to improve the image of the city had not been worked out effectively.